1989
DOI: 10.1093/jnci/81.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Growth of Human Lung Adenocarcinoma Cell Lines by Anti-Transforming Growth Factor-  Monoclonal Antibody

Abstract: We previously reported that two human lung adenocarcinoma cell lines (A-549 and PC-9) produce human transforming growth factor-alpha (hTGF-alpha) and express its receptors. In the present study an exogenously added monoclonal antibody against recombinant hTGF-alpha inhibited growth of these cell lines in vitro. This result indicated that endogenous hTGF-alpha produced by the cancer cells can function as an autocrine growth factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…TGFa binds to the EGFr with similar actions to those on binding of EGF with its receptor (Reynolds et al, 1981). Imanishi et al showed that an exogenously added monoclonal antibody against hTGFa inhibited growth of hTGFa producing lung adenocarcinoma cell lines in vitro (Imanishi et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…TGFa binds to the EGFr with similar actions to those on binding of EGF with its receptor (Reynolds et al, 1981). Imanishi et al showed that an exogenously added monoclonal antibody against hTGFa inhibited growth of hTGFa producing lung adenocarcinoma cell lines in vitro (Imanishi et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…33 Previous therapeutic approaches designed to abrogate TGF-␣ in vitro have included the use of neutralizing antibodies or antisense oligonucleotides. TGF-␣ monoclonal antibody treatment has been shown to inhibit the growth of lung cancer cell lines, 38 chemically induced mouse intestine cancer cells, 39 and human colon cancer cell lines in vitro. 40 DNA synthesis is reportedly decreased in both HNSCC cells 41 and ovarian cancer cells 26 following TGF-␣ antibody treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of EGFr activation in the regulation of TGFa, either by EGF or TGFa itself, has been established by the use of EGFr antibodies (Markowitz et al, 1990;Ennis et al, 1989;Imanishi et al, 1989). Although the TGFa promoter has been isolated, little is known about the mechanism of response to EGFr activation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of neutralizing antibodies to both TGFa and the EGFr, and TGFa antisense approaches have all demonstrated that TGFa is an autocrine growthstimulatory factor in colon carcinoma (Markowitz et al, 1990;Burgess, 1991, 1992;Ziober et al, 1993) as well as other tumors Ennis et al, 1989;Imanishi et al, 1989;Malden et al, 1989;Lee et al, 1991). TGFa has also been shown to be an autocrine growth factor in normal cells (Markowitz et al, 1990;Malden et al, 1989;Co ey et al, 1987;Madtes et al, 1988;Bates et al, 1990;Kudlow and Bjorge, 1990;Lewis et al, 1990) and during development (Wilcox and Derynck, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation